Variasi Morfologi dan Karakteristik Molekuler Isolat Phytophthora palmivora dari Beberapa Area Pertanaman Kakao serta Virulensinya Pada Kakao Klon Sulawesi 2 - Kuswinanti, Tutik; Patandjengi, Baharuddin; Melina; Hardina, Nur (Jurnal Fitopatologi Indonesia, 2023)
Morphological characterization of Phytophthora isolates commonly was done on the basis of the colony and hyphal swelling characteristics, form, and shape of chlamydospore, sporangia as well as oogonia and antheridia. Molecular characterization was conducted using specific primer pairs Pal1 s and Pal2a for Phytophthora palmivora and universal primer ITS4 and ITS5 followed by sequencing of isolates. The virulence of Phytophthora palmivora isolates was tested on a cocoa pod of the Sulawesi2 clone. A total of 21 Phytophthora isolates were collected from Palopo, Gowa, and Pinrang Districts. Based on colony morphology and microscopic features i.e. chlamydospore, sporangium, and its papilla form, all isolates indicated Phytophthora palmivora. Molecular identification using a specific primer showed that all ten representative group isolates had the same band in size of 650 bp, whereas using universal ITS4 and ITS5 primers, all isolates generated one band in the size of 900bp. The sequencing result showed, that all isolates were placed in the group P. palmivora. The virulence of P. palmivora isolates on the Sulawesi2 clone revealed a varying degree of virulence, from less virulent to highly virulent. All isolates from Pinrang were classified as highly virulent because induced necrotic in more than 50% of the tested cocoa pod.